Determinación de la coinoculación con hongos micorrízicos y bacterias diazotróficas en maíz bajo invernadero - Ávila Moncayo, Marlene Paulina (2015)
This research aims to isolate and characterize morphologically mycorrhizal fungi from the rhizosphere of maize. In addition it aims to determine the compatibility and co-inoculation of isolated diazotrophic bacteria and mycorrhizal fungi on morphological parameters and biomass in corn crop variety INIAP 182. During the isolation and morphological characterization three fungal genera were identified: Rhizopussp., Penicillium sp., and Aspergillus sp. Of these, the isolated (Cfung5-Penicillium sp.) and (Cfung13-Rhizopus sp.) manifested the highest phosphorus solubilisation in a Pikovskaya agarculture and positive compatibility in a bacteria-fungus growth. To corroborate the positive effect of the diazotrophic bacteria co-inoculation and the mycorrhizal fungi, acompletely randomized greenhouse experiment with seven treatments and nine replicates was set up.These treatments were T1 (fertilization), T2 (Penicilliumsp), T3 (Rhizopus sp.) T4 (control), T5 (Azotobacter vinelandii), T6 (Penicilliumsp + Azotobactervinelandii) and T7 (Rhizopussp + Azotobacter vinelandii).In general with respect to the morphological parameters, plant height, leaf number and diameter stem at 15, 30, 45, 60 and 90 (DDS) and biomas parameters (PFF, PSF, PSR and PFR), the best results were obtained with the isolated inoculation (Penicilliumsp + Azotobactervinelandii). With these positive results the beneficial effect of co-inoculation of diazotrophic bacteria and mycorrhizal fungi in the maturation and development of the corn crop is therefore validated.